ANALISIS MOTIVASI PASIEN BPJS DAN PASIEN UMUM TERHADAP PELAYANAN DI KLINIK JEPUN KURIPAN KABUPATEN LOMBOK BARAT TAHUN 2024 - Putri Amelia Silvi; Syatriawan Perdana Putra (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2024)
The aim of this research is to analyze the motivation of BPJS patients and general patients towards services at the Jepun Kuripan Clinic in West Lombok in 2024. And the specific aim of this research is to describe the motivation of BPJS patients and general patients at the Jepun Kuripan Clinic in West Lombok in 2024, to describe the quality of service received by BPJS patients and general patients at Jepun Kuripan Clinic, West Lombok in 2024. Analyzing the relationship between Motivation and Service Quality received by BPJS patients and general patients at Jepun Kuripan Clinic, West Lombok in 2024. The research design that will be used in this study is an analytical observational research design with a cross-sectional approach. The population of this study were all patients who sought treatment and received health services, both BPJS patients and general patients at the Jepun Kuripan Clinic, West Lombok. The number of samples in this study was